2022
DOI: 10.1126/science.abn5648
|View full text |Cite
|
Sign up to set email alerts
|

The human disease gene LYSET is essential for lysosomal enzyme transport and viral infection

Abstract: Lysosomes are key degradative compartments of the cell. Transport to lysosomes relies on GlcNAc-1-phosphotransferase-mediated tagging of soluble enzymes with mannose 6-phosphate (M6P). GlcNAc-1-phosphotransferase deficiency leads to the severe lysosomal storage disorder mucolipidosis II (MLII). Several viruses require lysosomal cathepsins to cleave structural proteins and thus depend on functional GlcNAc-1-phosphotransferase. Here, we used genome-scale CRISPR screens to identify Lysosomal Enzyme Trafficking fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 67 publications
0
24
0
1
Order By: Relevance
“…The present study provides a mechanistic explanation for disease-associated LYSET variants and suggests that loss-of-function mutations in LYSET could underlie mucolipidosis II and III cases that lack mutations in other components of the GlcNAc-1-phosphotransferase complex. Two recent CRISPR screens identified LYSET as required for viral infections ( 26 ) and turnover of lysosomal membrane proteins ( 27 ). These findings further highlight the importance of LYSET in diverse physiological and pathological processes where lysosomal catabolism plays a critical role.…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides a mechanistic explanation for disease-associated LYSET variants and suggests that loss-of-function mutations in LYSET could underlie mucolipidosis II and III cases that lack mutations in other components of the GlcNAc-1-phosphotransferase complex. Two recent CRISPR screens identified LYSET as required for viral infections ( 26 ) and turnover of lysosomal membrane proteins ( 27 ). These findings further highlight the importance of LYSET in diverse physiological and pathological processes where lysosomal catabolism plays a critical role.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the occurrence of Golgipathies tells us that this tagging mechanism takes place in the GC and its defective machinery leads to human diseases. A series of recent studies has highlighted the key role of TMEM251/LYSET/GCAF in the M6P pathway [3][4][5] . TMEM251 is a gene encoding a cis-Golgi transmembrane protein in which mutations have recently been identified in patients with severe recessive skeletal dysplasia associated with metabolic abnormalities 6 .…”
Section: Tmem251 a New Key Piece In The Mannose-6-phosphate Pathwaymentioning
confidence: 99%
“…The elucidation of the function of TMEM251 and of its key role in the M6P pathway came from three concomitant CRISPR screens. CRISPR screening to uncover proteins critical for reovirus infection, which requires lysosomal cathepsins activity to mediate disassembly of the viral particles 5 . The three studies demonstrated that knockingout of TMEM251 led to many defects related to lysosomal functions.…”
Section: Tmem251 a New Key Piece In The Mannose-6-phosphate Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The core mechanism underlying amino acid metabolic adaptations in cancer cells to grow in a nutrient-deficient tumor microenvironment (TME) was recently reported, and LYSET (TMEM251) and other amino acid utilizationassociated genes (ATF4, TSC2, VPS18, RAB7A, SLC7A5, SLC3A2, TGFBRAP1, GNPTAB, and GCN2) have been primarily screened out mainly through CRISPR-Cas9 based high-throughput method (Pechincha et al, 2022). Although these key players essential for tumor cell proliferation in harsh TME conditions and LYSET invovled in lysosomal biogenesis have been uncovered in the latest studies (Pechincha et al, 2022;Richards et al, 2022), their impact on pan-cancer clinical outcomes remains unknown. The metabolic status of amino acids in HCC patients with different immune subtypes according to HBV pathogenesis-relevant immunosignals is worthy of further study.…”
Section: Introductionmentioning
confidence: 99%